ANALYSIS OF FEASIBILITY OF MURABAHAH SELLING PRICES IN CONFORMITY TO THE MUI FATWA (Case Study of the Salimah Multi-Business Cooperative in Singkawang City) - nuryani, winda nuryani (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2024)
This thesis is the result of research that discusses the appropriateness of the murabahah selling price for the suitability of the MUI DSN Fatwa in the Salimah multi-business cooperative (KUSUMA) in Singkawang City. This research refers to sharia cooperatives carrying out their business based on Islamic law in accordance with the applicable regulations issued by the MUI DSN Fatwa which is also regulated in Law No. 2 of 1992 article 87 paragraph 3 concerning cooperatives where cooperatives can run their business on the basis of economic principles. sharia. One of them is in buying and selling transactions that use the Murabaha selling price system. Sharia cooperatives must state the selling price held by both parties in principle which includes the range of initial value and margin desired as a profit from the sharia system. In order to avoid incidents that become risk factors in murabahah transactions, it is necessary to determine standard prices.Keywords: Sharia Cooperative; Murabahah Selling Price, Margin, DSN MUI Fatwa